Analyzing affective societies : methods and methodologies - Kahl, Antje (London : Routledge, 2019)
In recent years, research in the social sciences and cultural studies has increasingly paid attention to the generative power of emotions and affects; that is, to the questions of how far they shape social and cultural processes while being simultaneously shaped by them. However, the literature on the methodological implications of researching affects and emotions remains rather limited. As a collective outcome of the Collaborative Research Center (CRC) Affective Societies at Freie Universiteat Berlin, Analyzing Affective Societies introduces procedures and methodologies applied by researchers of the CRC for investigating societies as affective societies. Presenting scholarly research practices by means of concrete examples and case studies, the book does not contain any conclusive methodological advice, but rather engages in illustrative descriptions of the authors' research practices. Analyzing Affective Societies unveils different research approaches, procedures and practices of a variety of disciplines from the humanities, arts and social sciences. It will appeal to students and researchers interested in fields such as Qualitative Research Methods, Emotions, Affect, Cultural Studies and Social Sciences.
13 Shared and divided feelings in translingual texts of Emine Sevgi Özdamar: performativity and affective relationality of language, writing and belongingPart IV Reflexivities; 14 Researching affects in the clinic and beyond: multi-perspectivity, ethnography, and mental health-care intervention; 15 'All Eyes Closed': dis/sensing in comparative fieldwork on affective-religious experiences; 16 Fieldwork, ethnography and the empirical affect montage; 17 Investigating emotions by using computer-assisted qualitative data analysis software: a methodological approach
OCLC-licensed vendor bibliographic record.
Keywords: Affect (Psychology) -- Social aspects; Emotions -- Sociological aspects; PSYCHOLOGY / Physiological Psychology; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General